Small-scale farmers in a 1.5 oC future: The importance of local social dynamics as an enabling factor for implementation and scaling of climate-smart agriculture - Martínez Barón, Deissy; Orjuela, Guillermo; Renzoni, Giampiero; Loboguerrero Rodriguez, Ana María; Prager, Steven D. (Elsevier, 2018)
Climate-smart agriculture (CSA) has the potential to help farmers implement both adaptation and mitigation practices. The mitigation aspect of CSA is often not considered by farmers due to a high discount rate and, as such, adaptation is usually the priority concern. This review article offers perspective on this issue and highlights two key gaps in the literature: (i) understanding of factors related to the uptake of adaptation practices with co-benefits for mitigation and, (ii) the role of social networks to better enable rapid, widespread implementation of CSA, the latter being critical to bringing CSA to scale. The systematic review treated literature on synergies between adaptation, mitigation and social networks in the rural sector, as well as case studies illustrating the importance of social networks in climate change interventions when addressing synergies in adaptation and mitigation. We find that additional research is required that explicitly focuses on how social networks and social capital may be harnessed to hasten the adoption and uptake of highly synergistic CSA practices. This will facilitate both adaptation in the near term and contribute to mitigation at scale, allowing small-scale farmers to both benefit from and contribute to a 1.5°C future.